Intimate Encounters: Screendance and Surveillance - White, John (The International Journal of Screendance, 2017)
<span style="color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">This article explores some ways in which screendance might invite a greater or deeper degree of kinesthetic empathy than is traditionally possible with live performance. In particular, the use of the close-up and the creation of editing rhythms are two strategies that extend screendance viewers' kinesthetic empathy into a more intimate relationship with the dance(rs). Furthermore, this article analyzes Katrina McPherson's screendance <em style="-webkit-print-color-adjust: exact; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px;">The Truth<span style="color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;"> as a case study in which this intimate viewing relationship is characterized by a kind of voyeurism shared with the act of viewing surveillance. I draw on some surveillance theory and artist Jill Magid's piece <em style="-webkit-print-color-adjust: exact; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px;">Evidence Locker<span style="color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;"> in order to explore the surveillance aspects of <em style="-webkit-print-color-adjust: exact; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px;">The Truth<span style="color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 22px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">.